Strategic problems in non-profit organizations : the Re-food 4 Good Association : case study - Matos, Maria Rita Advirta da Silva (2018)
The purpose of this paper is to provide insights into the real challenges and opportunities that exist in day-to-day operations of a non-profit organization. Through in-depth analysis of one such organization, guidelines and best-practices can be established to help others attempting similar pursuits. The case studies the Re-food 4 Good Association and is a useful tool for instructors looking to debate reasons for the success of some projects over others, challenges faced by social projects in general and discuss successful growth strategies. The organization is facing problems related to its fast-paced growth and is challenged to find ways to deal with the implementation of its mission and vision, while maintaining its most relevant critical success factors the most relevant of which being the micro-local nature of the project. The main conclusion is that the best way to achieve long-term sustainability and scalability is to find a balance between the uniqueness of each Operation Center and control from the Central Services. Given the fact that volunteers are at the center of Re-food’s success, is it explained how local issues and ways of operating on a daily basis should be left to each OC’s responsibility, keeping its uniqueness. Core issues such as expansion, brand image, communication and initial financial needs should be the responsibility of the central structure. The Case Study is followed by a Literature Review of relevant topics and a Teaching Note intended to help instructors for in-class use of the Case.